2007
DOI: 10.1007/s00508-007-0824-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein lipase HindIII polymorphism influences HDL-cholesterol levels in statin-treated patients with coronary artery disease

Abstract: HDL-C may be influenced by an interaction between statin treatment and LPL HindIII genotype. However, the effect of this interaction appears to be small when compared with the effect of non-genetic factors. This finding requires replication in a pharmacogenetic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
4
0
3
Order By: Relevance
“…Îäíàêî âëèÿíèå ãå-íîòèïà íà ýôôåêòèâíîñòü ãèïîëèïèäåìè÷åñêîé òåðà-ïèè ðàçëè÷íûìè êëàññàìè ïðåïàðàòîâ, â òîì ÷èñëå ñòàòèíàìè, êàê ïðåïàðàòàìè âûáîðà, èçó÷åíî íåäîñòà-òî÷íî. Âî-ïåðâûõ, ïðîâåäåíî íåáîëüøîå êîëè÷åñòâî ïðîñïåêòèâíûõ èññëåäîâàíèé ñ öåëüþ îïðåäåëåíèÿ ãå-íîòèïîâ, àññîöèèðîâàííûõ ñ èçìåíåííûì ëåêàðñòâåí-íûì îòâåòîì ïðè ïðèìåíåíèè ñòàòèíîâ [12]. Òàê, àâòî-ðû [12] âûÿâèëè ñòàòèñòè÷åñêè çíà÷èìîå âçàèìîäåéñò-âèå ìåaeäó ïîëèìîðôèçìîì HindIII ãåíà LPL è ýôôåê-òèâíîñòüþ ëå÷åíèÿ ñòàòèíàìè.…”
Section: ââåäåíèåunclassified
See 2 more Smart Citations
“…Îäíàêî âëèÿíèå ãå-íîòèïà íà ýôôåêòèâíîñòü ãèïîëèïèäåìè÷åñêîé òåðà-ïèè ðàçëè÷íûìè êëàññàìè ïðåïàðàòîâ, â òîì ÷èñëå ñòàòèíàìè, êàê ïðåïàðàòàìè âûáîðà, èçó÷åíî íåäîñòà-òî÷íî. Âî-ïåðâûõ, ïðîâåäåíî íåáîëüøîå êîëè÷åñòâî ïðîñïåêòèâíûõ èññëåäîâàíèé ñ öåëüþ îïðåäåëåíèÿ ãå-íîòèïîâ, àññîöèèðîâàííûõ ñ èçìåíåííûì ëåêàðñòâåí-íûì îòâåòîì ïðè ïðèìåíåíèè ñòàòèíîâ [12]. Òàê, àâòî-ðû [12] âûÿâèëè ñòàòèñòè÷åñêè çíà÷èìîå âçàèìîäåéñò-âèå ìåaeäó ïîëèìîðôèçìîì HindIII ãåíà LPL è ýôôåê-òèâíîñòüþ ëå÷åíèÿ ñòàòèíàìè.…”
Section: ââåäåíèåunclassified
“…Âî-ïåðâûõ, ïðîâåäåíî íåáîëüøîå êîëè÷åñòâî ïðîñïåêòèâíûõ èññëåäîâàíèé ñ öåëüþ îïðåäåëåíèÿ ãå-íîòèïîâ, àññîöèèðîâàííûõ ñ èçìåíåííûì ëåêàðñòâåí-íûì îòâåòîì ïðè ïðèìåíåíèè ñòàòèíîâ [12]. Òàê, àâòî-ðû [12] âûÿâèëè ñòàòèñòè÷åñêè çíà÷èìîå âçàèìîäåéñò-âèå ìåaeäó ïîëèìîðôèçìîì HindIII ãåíà LPL è ýôôåê-òèâíîñòüþ ëå÷åíèÿ ñòàòèíàìè. Òåì íå ìåíåå âëèÿíèå ýòîãî âçàèìîäåéñòâèÿ îêàçàëîñü ñëàáûì â ñðàâíåíèè ñ ýôôåêòîì "íåãåíåòè÷åñêèõ" ôàêòîðîâ (ïîë, íàëè÷èå ñàõàðíîãî äèàáåòà â àíàìíåçå).…”
Section: ââåäåíèåunclassified
See 1 more Smart Citation
“…Genome-wide association studies have identified numerous loci for the CAD and one of the main susceptibility loci is placed at chromosome 15q26.1 which exists the single nucleotide polymorphism in the form of rs17514846 ( Yang et al, 2020 ). Several case-control and meta -analysis studies have shown the relation between LPL gene and CAD ( Xu et al, 2019 , Javorsky et al, 2007 , Daoud et al, 2013 , Fischer et al, 2018 , Ma et al, 2018 , Shahid et al, 2017 , Xie, 2017 ). The accurate genetic and molecular or any other mechanism which affects the LPL and human disease is poorly understood and LDL was interrelated towards certain heterogenous disorders which involve limited cardiovascular disorders ( Hartley et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, genetic and environmental factors leading to decreased or increased activity of LPL may result in a respective decrease or increase of the HDL-cholesterol levels. LPL (495 T/G, rs320) polymorphism was also shown to influence HDL cholesterol levels in patients with coronary artery disease (CAD) (19,25). The TG metabolism was also shown to be influenced by PPARα.…”
Section: Introductionmentioning
confidence: 99%